Achados anatomopatológicos em perdizes (Rhynchotus rufescens) criadas em cativeiro - Momo, Claudia; Garrido, Eduardo; Werther, Karin [UNESP] (Universidade de São Paulo. Agência de Bibliotecas e Coleções Digitais, 2016)
The red-winged tinamou (Rhynchotus rufescens), a bird from the Tinamidae family, can be easily adapted to captivity. It is considered suitable for producing good quality meat while presenting great feed conversion rate, characteristics that make it interesting for commercial production. Therefore, in order to determine the major diseases that affect these birds, 114 birds from two different aviary types that died over a 12-year period, 1994-2006, were analyzed macro-and microscopically. Anatomical and pathological examinations showed that the most frequently affected systems were the urinary and digestive tracts. In the urinary tract, the main finding was gout, followed by amyloidosis and parasitism by the trematode Paratanaisia confusa. In the digestive tract, the presence of foreign material and parasitism by Capillaria penidoi were observed in the esophagus and crop. This study aims to describe the main anatomical and pathological findings in captive-bred red-winged tinamou and correlate them with the aviary type.
Anatomopathological findings in captive-raised redwinged tinamou (Rhynchotus rufescens)
Keywords: Amyloidosis; Capillaria penidoi; Paratanaisia confuse; Uric gout